On wind turbine's loss of synchronisation during severe faults. Issue 8 (13th May 2022) - Arasteh, Amir; Cutululis, Nicolaos A.
Abstract: Grid codes mandate that wind turbines (WTs) remain connected even during severe faults. This requirement can lead to WTs' loss of synchronisation (LoS) with the AC grid under severe symmetrical faults. In this paper, the LoS is illustrated by the power balance principle. Then, a solution with improved performance for avoiding LoS during severe faults is proposed, implemented and verified by simulations. The results show that the solution eliminates the steady‐state frequency deviation during faults, resulting in a smoother WT transient during and post‐fault.